Formulation and evaluation of matrix tablets of miglitol using different grades of HPMC - Yadav, Prof. Narendra (Asian Journal of Pharmaceutics (AJP), 2014)
Miglitol is a secondâ€generation â€glycosidase inhibitor with a chemical structure of 1â€desoxynojiromycin. It acts as a potent competitive inhibitor of the alfa glycosidase in the microvilli of the intestinal brush border. Miglitol has a shortÂ biological halfâ€life (2 h) and its bioavailability is >90%. Moreover, the site of absorption of miglitol is in the intestine.Therefore,Â the objective of the present work is to develop a sustained release matrix drug delivery systemfor the drug miglitol for theÂ better management of the disease, to minimize sideâ€effects as well as to improve patient compliance using different grades ofÂ HPMC Kâ€4, HPMC Kâ€15 and HPMC Kâ€100 in different proportions and combinations by the direct compression technique. Key words: Bioavailability, controlled release, direct compression technique, hydrophilic polymer, miglitol